Efektifitas Scaling Dan Root Planing Pada WanitaMenopause Penderita Periodontitis(Tinjauan Pada Poket Periodontal Di PosyanduLansia Mawar Xii Kelurahan PajangKecamatan Laweyan) - Nurhabibah, Gina; , drg. Edi Karyadi, M.M (2016)
Background: menopause is a natural life cycle which will be a decrease in estrogen levels to almost zero. The loss of estrogen will cause symptoms that arise one of which is a problem in the oral cavity that will happen periodontal tissue damage, such as periodontitis. Periodontitis is the most disease affects of humans, but the disease is often undiagnosed because they do not cause complaints, pproximately 15% of adults aged 21-50 years and 30% in people over 50 years old suffering from severe Periodontitis. One of the pathophysiological as incurred periodontitis that is the periodontal pocket. Treatment of periodontal tissues to reduce periodontal pocket depth in patients with periodontitis in postmenopausal women Posyandu Mawar village Pajang XII District of Laweyan that scaling and root planing is important. Purpose: to know whether effective scaling and root planing in periodontal pocket depth decrease in menopausal women patients with periodontitis. Methods: The sampling technique used purposive sampling. This study was conducted two inspections before and after SRP using the parameters Probing Pocket Depth (PPD) with a sample of 10 patients with periodontitis in postmenopausal women aged 45-69 years. Results: showed before the SRP has a pocket depth> 3mm of 6 people (60%) severe category and pocket depth <3mm were 4 people (40%) mild category. Meanwhile, after SRP with wakru term for 2 weeks had pocket depths> 3mm by 2 people (20%) severe category and pocket depth <3mm 8 people (80%) mild category. In this case proves the tissue repair characterized by a decrease in periodontal pocket depth with P = 0.000. Conclusion: scaling and root planing effectively against reduction in periodontal pocket in menopausal women patients with periodontitis. Keywords: Menopause, Periodontal Pocket, Scaling and Root Planing